A forensic anthropological investigation of skeletal remains recovered from a 1000 year old archaeological site in North Western Namibia - Rossouw, Lache Zolyn (Division of Anatomical Pathology, 2014)
Human and faunal skeletal remains were found scattered around the base of a talus cone at the bottom of a 30 metre sinkhole at Khoraxa-ams northwest of the Central Namib Desert. Subsequent dating of the site indicated that the remains had been deposited in the cavern in the order of a thousand years ago. The aim of this study was to examine skeletal remains recovered from the site and draw possible conclusions as to who they were and the circumstances surrounding their deposition in the cave. A forensic analytical approach was utilized to uncover the evidence, allowing us to manage the site as a 'crime scene.' This approach included determining the MNI, constructing a demographic profile and analysing post-mortem preservation as well as posing questions vital to forensic investigations including ante-mortem features that could lead to the ethnic identification of unknown individuals and the peri-mortem circumstances surrounding the deposition of the remains. Sixteen individuals, based on cranial bone representation were identified in the sample, consisting of only adult individuals with the exception of one sub-adult, and a male to female ratio of roughly 1:1. The people of Khoraxa-ams were of Negroid ancestry, consumed a mixed diet of gathered and agricultural foods, were in fairly good health at the time of their death, showed signs of involvement in low-impact labour and practiced dental modification. Their most likely identity, based on these biological markers, lifestyle observations and cultural practices, is a group similar or ancestral to the modern Herero of Namibia. The exact nature and circumstance surrounding the cause of death is unknown. Based on the extent of skeletal injuries, it is likely that they received peri-mortem blunt force trauma and post-mortem trauma after death by being dropped into the 30 metre cave. It is speculated, given the demographic profile of women and children presenting with more severe blunt force trauma, the lack of defence wounds and the fact the individuals were dead before being dropped in the cave, that the site at Khoraxa-ams represents an execution location, though no secure evidence exists to support this theory. The forensic approach to this study has enabled the identification of otherwise unknown archaeological remains, and has also provided insight into a period of Namibian history where relatively little is known.